Pengembangan keterampilan sosial dalam organisasi kemahasiswaan himpunan mahasiswa program studi (HMPS) Tadris Ilmu Pengetahuan Sosial Universitas Islam Negeri Sultan Syarif Kasim Riau - Triana, Puput; Susanti, Emilia; Patilla, Nur; Rindiyani, Riski; Pratama, Wahyudha; Hidayat, Putra; Saputra, Akmal Hakim (Karoteh Utama, 2024)
This research aims to develop social skills within student organizations, specifically the Himpunan Mahasiswa Program Studi (HMPS) Tadris Ilmu Pengetahuan Sosial at Universitas Islam Negeri Sultan Syarif Kasim Riau. The study employs a qualitative methodology, utilizing interviews, observations, and document analysis. Interviews were conducted with HMPS members and administrators to gain in-depth insights into their experiences and perspectives on the essential social skills cultivated within the organization. Observations were made to directly observe interactions during organizational activities such as meetings, discussions, and events. Documentation was used to collect data from various official organizational documents such as meeting minutes, activity reports, and organizational guidelines. The findings indicate that social skills, including effective communication, teamwork, and adaptability, are crucial and are actively developed within HMPS Tadris IPS. Members enhance these skills through active participation in sports, training, and mentorship activities. The study concludes that organizations like HMPS Tadris IPS play a vital role in developing students' social skills, which are beneficial not only in academic settings but also in their future professional lives.